Criminal Responsibility of Children Who Commit the Crime of Allowing, Ordering to Do or Participating in Violence Against Children Until Death Based on Indonesian Criminal Law - Jufnidar; Niru Anita Sinaga; Sujono (International Journal of Science and Society, 2023)
A criminal act is an act of a person of his own free will or of another person committed by him and this behavior is an act that is prohibited so that a criminal liability arises from the act itself. Any action against a child which results in physical, psychological, sexual misery or suffering and/or neglect, including threats to commit acts, coercion or deprivation of liberty by way of violation of the law is a criminal act of violence against children. A child who commits a crime permits, commits, orders to commit or participates in committing violence against children to the point of death must still be held responsible because it is impossible for a person to be held accountable and sentenced if he does not commit a crime. To be further investigated how to regulate the crime of children who commit, order to commit or participate in violence against children to death based on Indonesian criminal law and what is the criminal responsibility of children who commit criminal acts to allow, order to commit or participate in violence against children to death. The research method used in this research is normative legal research method. From the results of the research, it was found that the regulation of juvenile offenses allows, orders, or participates in violence against children to death in Article 76C in conjunction with Article 80 Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection and the criminal responsibility of children who commit crimes allowing, ordering to commit or participating in violence against children to death by serving a maximum of half of the maximum sentence of imprisonment for adults as stipulated in Article 81 paragraph (2) of Law Number 11 Years 2012 concerning the Juvenile Criminal Justice System. Clarifying the meaning of acts of violence in the Criminal Code, Legislation, Government Regulations, Permenkumham and the Government must establish legislation, government regulations, Permenkumham to be even more assertive in imposing sanctions on perpetrators of violence against children.